2019
DOI: 10.1002/adfm.201808737
|View full text |Cite
|
Sign up to set email alerts
|

Piezotronic Effect Enhanced Plasmonic Photocatalysis by AuNPs/BaTiO3 Heterostructures

Abstract: Piezopotential-assisted catalysis is of great significance for low cost and efficient catalysis processes. Here, Au x /BaTiO 3 plasmonic photocatalysts are fabricated by precipitating Au nanoparticles on piezoelectric BaTiO 3 nanocubes through a chemical approach. The Au nanoparticles (<8 nm) are decorated uniformly on the surface of BaTiO 3 , which endows the heterostructure with a wide light absorption from 300 to 600 nm. The photocatalytic properties of the heterostructures are investigated in detail toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
103
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 190 publications
(113 citation statements)
references
References 41 publications
(44 reference statements)
0
103
0
Order By: Relevance
“…Some researchers focused on the interaction of BaTiO 3 and metals or electrocatalysts, such as Al, Au, Ag, etc., [ 106,111–113 ] and further clarified the mechanism of the coupling effect between piezotronics and surface plasmonic resonance. [ 33 ] For example, Xu et al reported Ag–BaTiO 3 piezo‐photocatalysts synthesized by a photochemical reducing approach.…”
Section: Piezoelectric Polarization Promoted Photo(electro)catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers focused on the interaction of BaTiO 3 and metals or electrocatalysts, such as Al, Au, Ag, etc., [ 106,111–113 ] and further clarified the mechanism of the coupling effect between piezotronics and surface plasmonic resonance. [ 33 ] For example, Xu et al reported Ag–BaTiO 3 piezo‐photocatalysts synthesized by a photochemical reducing approach.…”
Section: Piezoelectric Polarization Promoted Photo(electro)catalysismentioning
confidence: 99%
“…By introducing Au nanoparticles, the visible‐light‐driven catalytic degradation of methyl orange by BaTiO 3 was much enhanced. [ 112 ] The cooperation of BaTiO 3 with other semiconductors such as ZnO/BaTiO 3 heterostructure has also been demonstrated to work well in the degradation of pollutants, which endows a suitable bend alignment formed at the interface to promote charge transfer behavior. [ 114 ]…”
Section: Piezoelectric Polarization Promoted Photo(electro)catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…To attest the ferroelectric property of BTO, the sample's XRD was checked ( Figure S7, Supporting Information), which describes that the phase of BTO has been changed from cubic to tetragonal (presence of ferroelectricity) by the splitting peaks. [39] From the TEM image, the size of annealed BTO is found to be 50 nm with a d-spacing of 0.231 nm attributed to (111) crystal plane (Figure 2e). Moreover, the selected area electron diffraction image makes known that the main crystal planes of BTO are (100), (110), (111), (211), and (320) (Figure 2f), but the (200) plane exhibits a tiny scattering, revealing that the crystal plane spacing is split and matched well with the XRD data.…”
Section: Doi: 101002/adma201902963mentioning
confidence: 99%
“…To attest the ferroelectric property of BTO, the sample's XRD was checked (Figure S7, Supporting Information), which describes that the phase of BTO has been changed from cubic to tetragonal (presence of ferroelectricity) by the splitting peaks . From the TEM image, the size of annealed BTO is found to be 50 nm with a d ‐spacing of 0.231 nm attributed to (111) crystal plane (Figure e).…”
mentioning
confidence: 99%